Cholecalciferol Prevent Obesity in Rats Under High Fat High Fructose Diet - Dea Anenta; Budiyanti Wiboworini; Muthmainah Muthmainah (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Obesity is an accumulation of fat body condition due to calories and energy imbalance. Obesity often coexists with low vitamin D status. Low vitamin D status is known to establish abnormality in lipid profile and increasing weight. This study aims to look at the effect of the dose and duration of Cholecalciferol supplementation on lipid profiles in male rats induced by high fat high fructose diet. In this study, we conducted an experiment using a randomized pre and posttest control group design. This study analyzed 3 groups of male Sprague Dawley strain rats that were induced with a high fat high fructose diet to become diet-induced obesity rats. Each group either receives cholecalciferol in the amount of 2.500 IU/200gr/day in P1 group, 5.000IU/200gr/day in P2 group, and 10.000 IU/200gr/day in P3 group for 8 weeks. Lipid profile outcomes analyzed include levels of total cholesterol, triglycerides, High-density lipoprotein (HDL), and low-density lipoprotein (LDL). Cholecalciferol supplementation resulted in significant differences between all lipid parameters. Total cholesterol levels are lowest in the P3 group with a mean of 102.09±2.45. followed by P2 (115.80±3.98) and P1 group (138.33±4.82), and highest in the control group (196.52±4.36). Triglyceride levels are also lowest in the P3 group with a mean of 76.03±3.81, followed by the P2 (115.80±3.98) and P1 (138.33±4.82) groups, with the highest in the control group (134.46±5.84). HDL levels are instead highest in the P3 group with a mean of 80.93±8.29, followed by P2 (77.98±10.38) and P1 (66.54±7.25) group, while lowest in the control group (25.45±2.32). LDL levels are lowest on the P3 group with a mean of 33.71±2.49, followed by P2 (38.72±1.41), and P1 (47.62±2.76) group, while highest in the control group with a mean of 82.96±1.88. Cholecalciferol supplementation was found to provide a beneficial effect across all lipid profile outcomes in this study such as total cholesterol, triglyceride, HDL, and LDL in high fat high fructose induced male Sprague Dawley rats.